The Effect of Workload on Employee Performance at PT. Mandiri Utama Finance, Tbk Sengkang Wajo Regency - Mansur Mansur; Andi Adawiah; Nurul Wahby (GENTARA: management and accounting research, 2025)
This study aims to analyze the effect of workload on employee performance at PT Mandiri Utama Finance, Tbk Sengkang, Wajo Regency. In this study, a quantitative approach was used with a correlational research design, which relates workload to employee performance through regression analysis. The research sample consisted of 28 employees working at the Sengkang branch, who were randomly selected. Data collection methods were conducted through questionnaires distributed to respondents, using a Likert scale to measure employees' perceptions regarding their workload and performance. The data collected was then analyzed using simple linear regression to determine the extent of the influence of workload on employee performance.The regression analysis results show that workload has a negative and significant effect on employee performance. The negative regression coefficient for the workload variable indicates that the higher the workload received by employees, the lower the resulting performance. This is due to stress and fatigue caused by excessive workload, which disrupts employee concentration and work quality. This finding illustrates that companies need to pay attention to managing workload wisely to prevent a significant decline in performance. Based on these findings, this study suggests that PT Mandiri Utama Finance, Tbk Sengkang Wajo Regency make adjustments to the workload given to employees. A more balanced and realistic workload management will help improve overall employee performance. In addition, companies are advised to provide time and resource management training, and ensure adequate support for employees in completing tasks well, without feeling burdened